2014
DOI: 10.1021/jo501432x
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Preparation of All-cis 1,3,4-Trifluoro-2-phenylcyclohexane, Avoiding a Phenonium Intermediate

Abstract: The original synthesis of all-cis 1,2,4,5,-tetrafluoro-2-phenylcyclohexane resulted in a trifluorocyclohexene as a significant co-product of the final fluorination step. This product was notable in that an elimination reaction was accompanied by C-F bond formation that had occurred with a retention of configuration. In order to deconvolute this reaction, the two isomers of the ditriflate diol precursor were separated, and they were each treated independently with Et3N·3HF. One gave the original all-cis 1,2,4,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…The structure and stereochemistry of product 18 was also confirmed by X-ray structure analysis as shown in Figure 2. In retrospect we can rationalize a rearrangement reaction, which most reasonably proceeded via a phenonium type intermediate as represented by 17 in Scheme 3 [5,[15][16][17][18][19][20]. This is an interesting outcome but not particularly useful for the preparation of a tetrafluorocyclohexyl motif.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The structure and stereochemistry of product 18 was also confirmed by X-ray structure analysis as shown in Figure 2. In retrospect we can rationalize a rearrangement reaction, which most reasonably proceeded via a phenonium type intermediate as represented by 17 in Scheme 3 [5,[15][16][17][18][19][20]. This is an interesting outcome but not particularly useful for the preparation of a tetrafluorocyclohexyl motif.…”
Section: Resultsmentioning
confidence: 99%
“…These diols could also be converted to their corresponding triflates 8 and 9. However when the triflates 8 and 9, which could be separated, were treated individually with 3HF.NEt 3 , then 8 gave 1 exclusively, and 9 gave cyclohexene 10 exclusively [5]. The stereochemistry of cyclohexene 10 indicated that the fluorination had occurred with retention of configuration, consistent with a rearrangement via the symmetrical phenonium ion 11 [5].…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations